An Awkward Aid: The Alliance for Progress in Chilean Graphic Humor, 1961–1962; Una Ayuda Incómoda: La Alianza Para el Progreso en el Humor Gráfico Chileno, 1961-1962 - Lacoste, P (Universidad de Playa Ancha -Departamento De Historia, 2025)
The Alliance for Progress, introduced in 1961 by the United States to promote economic and social development in Latin America and counter the influence of the Cuban Revolution during the Cold War, sparked intense debates in Chile about its motivations and implications, reflected in the media across the political spectrum. This article analyzes how political cartoons published between 1961 and 1962 in left-wing, right-wing, and centrist Chilean newspapers and magazines represented these tensions, revealing an ambivalent and often critical reception of the U.S. initiative. Through political cartoons, understood as cultural artifacts, narratives emerge that express discomfort with the cooperation proposal, anticipating the ideological disputes that would shape Chile’s political history in the following decades. This research is part of an effort to approach the Cold War from unconventional perspectives, helping to decentralize the analysis of the global conflict and better understand Chile’s critical position within that context. © 2025 Universidad de Playa Ancha -Departamento De Historia. All rights reserved.